YOUNG CONSUMERS’ GREEN PURCHASING BEHAVIOR: THE INFLUENCE OF ENVIRONMENTAL AWARENESS AND GREEN MARKETING - Warmadewa, Dimas Yudhayana; Paramita, Eristia Lidia (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The increase in the amount of waste is highlighting a fairly high problem in Indonesia nowadays. With the awareness of this problem, many manufacturers have started to create environmentally friendly products such as stainless steel straws. The stainless steel straw is quite a breakthrough to start the market using a green marketing strategy. This study aims to determine the effect of environmental awareness and green marketing on purchasing decisions of young consumers on stainless steel straws. The approach used in this research was quantitative. The populations in this study were students who have used stainless steel straws. There were 345 respondents. The purposive sampling technique was used to obtain data, with criteria: 1) ever bought a stainless steel straw; (2) 18-22 years old. The data analysis was multiple linear analysis test. The results of this study indicated that environmental awareness has no effect on purchasing decisions, while green marketing has an effect on purchasing decisions. Keywords : Environmental awareness, green marketing, purchasing decisions, young consumers